1
$\begingroup$

Last week I wrote a test on exponential equations and I came across this problem;

$$10*4^x-21*10^x=10*25^x$$

But I could not found a way to solve it, because it has different bases, which I cannot make the same. Here is what I came up with:

$$10*2^{2x}-21*2^x*5^x=10*5^{2x}$$

Here I only have 2 bases. I tried to solve it with two changes:

$$2^x=a$$ $$5^x=b$$

And then I got this equation $$10a^2-21ab=10b^2$$

That is the furthest I managed to come. Of course I do not know if this is even correct.
Also I have seen on the internet such methods as using logarithms, but we have not taken this course yet, so it is not a solution I am looking for.

$\endgroup$
  • $\begingroup$ Homogeneous quadratic equations in two variables are solved in basically the same way as ordinary quadratic equations in one variable. (homogeneous means every monomial has the same degree) $\endgroup$ – user14972 Jan 16 '18 at 19:08
  • $\begingroup$ You are on the right track, go ahead. $\endgroup$ – Yves Daoust Jan 16 '18 at 19:13
  • $\begingroup$ $10 a^2 - 21 a b - 10 b^2 = 0.$ If that is not enough (it factors) you can divide through by $b^2,$ make a varaible $c = a/b,$ giving $10c^2 - 21 c - 10 = 0,$ and use the quadratic formula if necessary. Note $841 = 29^2$ $\endgroup$ – Will Jagy Jan 16 '18 at 19:27
2
$\begingroup$

write your equation in the form $$10-21\left(\frac{5}{2}\right)^x=10\left(\left(\frac{5}{2}\right)^x\right)^2$$ and Substitute $$t=\left(\frac{5}{2}\right)^x$$ and solve a quadratic equation

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

There's nothing wrong with what you've done so far. Just to carry it on, we have $$10a^2-21ab-10b^2=0,$$ that is $$10a^2+4ab-25ab-10b^2=0,$$

that is

$$2a(5a+2b)-5b(5a+2b)=0,$$

so $$10a^2-21ab-10b^2=0 \Rightarrow (2a-5b)(5a+2b)=0.$$

This then implies

$$2a=5b,\quad 5a=-2b,$$ undoing your change of variables for the first expression

$$2\cdot 2^x=5\cdot 5^x,$$ that is $$\frac{5}{2}=\Big(\frac{2}{5}\Big)^x,$$

so $$x=-1.$$ For the second expression, we undo the change of variables $$5\cdot 2^x=-2\cdot 5^x,$$ that is $$-\frac{2}{5}=\Big(\frac{2}{5}\Big)^x,$$

which can never hold true. Thus, the solution is $$x=-1.$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.